2013
DOI: 10.1287/mksc.1120.0720
|View full text |Cite
|
Sign up to set email alerts
|

How to Price Discriminate When Tariff Size Matters

Abstract: Firms that serve a large market with many diverse consumer types use discriminatory or nonlinear pricing to extract higher revenue, inducing consumers to separate by self-selecting from a large number of tariff options. But the extent of price discrimination must often be tempered by the high costs of devising and managing discriminatory tariffs, including costs of supporting consumers in understanding and making selection from a complex menu of choices. These tariff design trade-offs occur in many industries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Many companies take the help of latest technologies to access real-time information and to take decisions. They use software to understand and analyze actual customer responses to different pricing schedules (Bagh & Bhargava, 2013). For example, merchants who sell their products on Amazon.com, change their prices regularly, sometimes on a daily or even hourly basis to reflect the demands of customers.…”
Section: Price Discriminationmentioning
confidence: 99%
“…Many companies take the help of latest technologies to access real-time information and to take decisions. They use software to understand and analyze actual customer responses to different pricing schedules (Bagh & Bhargava, 2013). For example, merchants who sell their products on Amazon.com, change their prices regularly, sometimes on a daily or even hourly basis to reflect the demands of customers.…”
Section: Price Discriminationmentioning
confidence: 99%
“…None of these studies, however, calculated the optimal three-part tariff plan. For example, Bagh and Bhargava (2013) analyzed the ability of alternative nonlinear pricing structures to price discriminate. They showed that three-part tariffs are more efficient than two-part tariffs as price-discriminating mechanisms for heterogeneous consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The parameter t for the type of the buyer is assumed to represent the valuation of a potential buyer for the good. The buyer derives a utility equal to t · u(A t ) − p t from acquisition of a quantity A t (allocation to buyer of type t) of the good, where u is a differentiable, strictly concave, strictly increasing function (u The non-linear pricing problem briefly described above occurs in many industries, e.g., wireless communication services, other telecom and technology products, legal plans, fitness clubs, automobile clubs and healthcare plans; see Bagh and Bhargava (2013) for further details. It is part of the general theory of basic static adverse selection problems in economics.…”
Section: The Settingmentioning
confidence: 99%
“…In this case, one can implement the optimal nonlinear payment schedule by offering a menu of two-part tariffs as discussed in Section 3.5 of Tirole (1990). In a recent paper Bagh and Bhargava (2013) study the efficiency of two and three-part tariffs and show that a relatively small menu of three-part tariffs may be more profitable than a menu of two-part tariffs of any size. In Section 2.3.1 of Bolton and Dewatripont (2004) the solution of the above problem is investigated under the so-called SpenceMirrlees single crossing condition on the utility function u, which helps simplify the problem by reducing the number of constraints considerably.…”
Section: Proposition 1 For Regular F There Exists An Optimal Direct mentioning
confidence: 99%